Respostas

2014-03-19T19:33:41-03:00
A)  x-x(x+1)=12-(3x-2)
     x -(x² + 1x) = -36 + 24
    x + x = 12
     2x = 12
       x = 6

b)
4 (y-2)+3(2y-1)= 6 (2y-3)
   4y - 8 + 6y - 3 = 12y - 18
  10y - 11 = 12y - 18
 10 y - 12y = -18 + 11
 -2y = -7 (multiplica por  -1)
 2y = 7
y = 3,5
Srta Lavínia, é 12 - (3x - 2) e não 12 * (3x - 2)
A melhor resposta!
2014-03-19T20:08:17-03:00
A) x - x (x + 1) = 12 - (3x - 2)
    x - x² - x = 12 - 3x + 2
   -x² - x + x + 3x - 12 - 2 = 0
  -x² + 3x - 14 = 0
  S =  Ф  pois Δ < 0 
B) 4 (y - 2) +3 (2y - 1)= 6 (2y - 3)
    4y - 8 + 6y - 3 = 12y - 18
    4y + 6y - 12y = -18 + 8 + 3
   -2y = -7
     y =  -
            -2
     y =  
            2
1 5 1